Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation terhadap Motivasi Belajar PAK Siswa Kelas IX di SMP Negeri 1 Simanin do, Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Angel Sri Wulan Manalu; Oktober Tua Aritonang; Risden Anakampun; Boho Pardede; Simion Harianja (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The aim of this research is to determine the positive and significant influence of implementing the Group Investigation Type Cooperative Learning Model on the Learning Motivation of PAK Class IX Students at SMP Negeri 1 Simanindo, Samosir Regency for the 2023/2024 Academic Year. The research method used is a quantitative method and a pre-experimental design research type in the form of